EFISIENSI TEKNIS USAHATANI TOMAT (Solanum lycopersicon) DENGAN PENDEKATAN STOCHASTIC FRONTIER DI KECAMATAN PRINGGASELA - Dimas Ilhami Saputra; Rini Endang Prasetyowati; Elwani Hidayati; Muhammad Anwar (AGROSCIENCE (AGSCI), 2025)
Fluctuations in production yields from year to year indicate potential problems in the efficient use of production factors. The objective of this study was to analyze the technical efficiency of tomato farming in Pringgasela District. The research locations were purposively selected, with three villages: Pengadangan, Aik Dewa, and Jurit Baru. Thirty farmer respondents were selected using quota sampling and distributed within each village using proportional random sampling. Data were analyzed using the Cobb-Douglas production function approach and the stochastic frontier model. The results showed that land area and labor had a significant and positive effect on tomato production, while seeds, fertilizers, and pesticides had no significant effect. The average technical efficiency score for tomato farmers was 0.893, indicating that most farmers were technically efficient. Socioeconomic factors influencing inefficiency included age, farming experience, and family burden. Older and more experienced farmers tended to be more efficient, while larger family burdens increased inefficiency. These results demonstrate the importance of empowering farmer groups and extension workers to promote training and implement appropriate cultivation technologies to increase tomato production efficiency in the research area